HYPHESSOBRYCON NATAGAIMA (CHARACIFORMES: CHARACIDAE) A NEW SPECIES FROM COLOMBIA, WITH A KEY TO THE MAGDALENA BASIN HYPHESSOBRYCON SPECIES - CARLOS A. GARCÍA-ALZATE; DONALD C. TAPHORN; CESAR ROMAN-VALENCIA; FRANCISCO A. VILLA-NAVARRO (Caldasia)
A new species, Hyphessobrycon natagaima, is described from the upper Magdalena River Basin in Colombia. It differs from all other species of Hyphessobrycon with a dark lateral stripe inhabiting the Magdalena River Basin: H. poecilioides, H. proteus and H. ocasoensis, by having eight to twelve pored lateral-line scales (vs. 14-26); four scales between the lateral line and the pelvic-fin insertions (vs. five or six); one tooth on the maxilla (vs. zero in H. poecilioides, and two to five in H. proteus; except H. ocasoensis, with one), a dark, interrupted, lateral stripe that is not in contact with the caudal peduncle spot (vs. absence of caudal spot in H. poecilioides, lateral stripe continued that is in contact with the caudal peduncle spot in H. ocasoensis). It has a rhomboid shaped caudal-peduncle spot that continues on to middle caudal-fin rays (vs. absence of caudal peduncle spot in H. poecilioides and caudal peduncle spot round and not continued on to middle caudal-fin rays in H. ocasoensis); and presence of hooks on all fins in mature males (vs. males with hooks on anal, pelvic and pectoral fins). Hyphessobrycon natagaima differs from H. ocasoensis, in addition to the above characters, by having four scale rows between the lateral line and the anal-fin origin (vs. six); three or four scale rows between the lateral line and the pelvic-fin insertions (vs. six); ten or eleven predorsal scales (vs. nine); i,9,i dorsal-fin rays (vs. ii,8,i); 18-20 branched anal-fin rays (vs. 21-22) and eleven branched pectoral-fin rays (vs. twelve). A key for the identification of Hyphessobrycon species present in the Magdalena River Basin is provided.